(untitled) - Lipton, Bruce H. (Carlsbad, Calif., 2008)
Author Lipton is a former medical school professor and research scientist. His experiments, and those of other leading-edge scientists, have examined in great detail the processes by which cells receive information. The implications of this research radically change our understanding of life. It shows that genes and DNA do not control our biology; that instead DNA is controlled by signals from outside the cell, including the energetic messages emanating from our positive and negative thoughts. Dr. Lipton's profoundly hopeful synthesis of the latest and best research in cell biology and quantum physics is being hailed as a breakthrough, showing that our bodies can be changed as we retrain our thinking.--From publisher description.
Keywords: Molecular biology,Cytology,Sinh học phân tử,Tế bào học